The effects foundation options have on the design of load-bearing tilt-up concrete wall panels - Schmitt, Daniel A. (Kansas State University, 2009)
Soils conditions vary throughout the United States and effect the behavior of the foundation system for building structures. The structural engineer needs to design a foundation system for a superstructure that is compatible with the soil conditions present at the site. Foundation systems can be classified as shallow and deep, and behave differently with different soils. Shallow foundation systems are typically used on sites with stiff soils, such as compacted sands or firm silts. Deep foundation systems are typically used on sites with soft soils, such as loose sands and expansive clays. A parametric study is performed within this report analyzing tilt-up concrete structures in Dallas, Texas, Denver, Colorado, and Kansas City, Missouri to determine the most economical tilt-up wall panel and foundation support system. These three locations represent a broad region within the Midwest of low-seismic activity, enabling the use of Ordinary Precast Wall Panels for the lateral force resisting system. Tilt-up wall panels are slender load-bearing walls constructed of reinforced concrete, cast on site, and lifted into their final position. Both a 32 ft (9.75 m) and 40 ft (12 m) tilt-up wall panel height are designed on three foundation systems: spread footings, continuous footings, and drilled piers. These two wall heights are typical for single-story or two-story structures and industrial warehouse projects. Spread footings and continuous footings are shallow foundation systems and drilled piers are a deep foundation system. Dallas and Denver both have vast presence of expansive soils while Kansas City has more abundant stiff soils. The analysis procedure used for the design of the tilt-up wall panels is the Alternative Design of Slender Walls in the American Concrete Institute standard ACI 318-05 Building Code and Commentary Section 14.8. Tilt-up wall panel design is typically controlled by lateral instability as a result from lateral loads combining with the axial loads to produce secondary moments. The provisions in the Alternative Design of Slender Walls consider progressive collapse of the wall panel from the increased deflection resulting from the secondary moments. Each tilt-up wall panel type studied is designed in each of the three locations on each foundation system type and the most economical section is recommended.
Keywords: Tilt-up wall panels; Spread footings; Continuous footings; Drilled piers; Structural design; Engineering, General (0537)